Kampus aba-abi growth strategy - Arifudin Anwar, Andi; S. Motik, Suryani (The Indonesian Journal of Business Administration, 2016)
Abstract â€” The Constitution of Republic of Indonesia in 1945 said that education for all Indonesian people, Academy of Foreign Language â€œINDONESIAâ€ LPI and Academy Bank of Indonesia â€œLPIâ€, known as Kampus ABA-ABI have participated in educating Indonesian people. Kampus ABA-ABI, which was established in 1965 by Yayasan Lembaga Pendidikan Indonesia, has graduated 70,000 professional executive for English and Banking Diploma Program. One thing of competitive advantage for Kampus ABA-ABI was one of the largest market share in DKI Jakarta in 1990 until 2000 with the amount of students, include University of Indonesia had 25,000 students, followed by Trisakti University had 20,000 students and Kampus ABA-ABI has 17,500 students. However, along with its development, Kampus ABA-ABI has decreased the amount of students from year-to-year. The conceptual framework provides a guideline in this study. The tools that used to explore business issues on internal factors are Value Chain Analysis and Business Model Canvas. Meanwhile, the external factors were using Porterâ€™s Five Forces Analysis and PEST analysis. After analyzing internal and external factors, it will be obtained Strength, Weakness, Opportunity and Threat which are summarized in SWOT analysis. This study literature uses the theories related to strategic management and business models as well as qualitative research methodologies such as direct observation and in-depth interviews with the owner and top executive of Kampus ABA-ABI to collect primary data. Based on those analyzes and in-depth interviews, decreasing the amount of Kampus ABA-ABIâ€™s student from year-to-year due to the business model is not clear. Business solutions proposed some strategies that should be developed by Kampus ABA-ABI that can meet the studentâ€™s needs as customers. Kampus ABA-ABI should use the strategy of product development and market penetration. For the next stage of strategic analysis, TOWS Matrix is used to create a new strategy within the business. Further, Kampus ABA-ABI should create new value propositions to students and implemented them into the new Business Model Canvas for the proposed new strategies. New strategies that have already proposed, should be pursued by Kampus ABA-ABI which are making promotions through direct channels and indirect channels as a new marketing strategies, training and rewards to employees and improve the quality of lecturer and studentsâ€™ learning process. These steps should be taken to reach Kampus ABA-ABIâ€™s success in attracting new customers and increasing profits and sales.Â Keyword: business strategy, business model, higher education, business model canvas